Memanusiakan Manusia: Eksplorasi Sastra Apokaliptik dan Panggilan Kemanusiaan Dalam Injil Matius 25:31-46 Melalui Semboyan ‘Sitou Timou Tumou Tou’ - Udang, Frety Cassia; Kalundang, Audriano (Tepian : Jurnal Misiologi dan Komunikasi Kristen, 2024)
The Current situation continuestondegenerate into apatheic and inhumane actions towards humanity. A lot of data is accessible that shows the level of dehumanitation occuring everywhere. So in this research the call to humanity will be studied in the light of the Gospel of Matthew 25:31-46 in the frame of the motto Si Tou Timou Tumou Tou. This research uses qualitative research methods with a descriptive approach. Because it uses biblical tekts, the approach used is an apocalyptic literary approach. The results of this research show that the text of Matthew 25:31-46 contains apocalyptic elements that are typical of the Gospel of Matthew, and the situation of serving the ‘despicable’ becomes a style of humanitarian service that must be carried out and lived. On the other side, Si Tou Timou Tumou Tou has becomes a lifestyle in creating a humanist living situation.